Analisis Peran Bea Materai dalam Validitas Surat Perjanjian - Haya Aghnia Azzara; Sherin Aulia Putri; Rendy Rizkysyah Lubis (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
This study aims to analyze the role and function of stamp duty in agreements in Indonesia. Stamp duty is one of the important elements in the document legalization process, which functions as evidence that an agreement has met the formal requirements set by law. In this study, qualitative methods were used to collect data through literature studies. The results of the study indicate that stamp duty not only functions as a source of state revenue, but also provides legal certainty for the parties involved in the agreement. In addition, this study identifies the challenges faced in the implementation of stamp duty, including low public understanding and potential legal disputes. This study is expected to contribute to the development of policies related to stamp duty and increase public awareness of the importance of legal aspects in agreements.-